Electroacupuncture: A New Approach to Open the Blood–brain Barrier in Rats Recovering from Middle Cerebral Artery Occlusion. Issue 6 (December 2018) - Zhang, Jiangsong; Lin, Xianming; Zhou, Hui; Chen, Yuanyuan; Xiao, Shuangkai; Jiao, Junyue; Zhao, Yibin; Di, Zhong
Objective: To examine for an opening effect on the blood–brain barrier (BBB) in intact rats and rats with experimental ischaemia-reperfusion (I/R) during the recovery period after various electroacupuncture (EA) treatments with different time courses, and to determine whether there is a time-dependent effect. An additional objective was to determine whether this method could induce the penetration of nerve growth factor (NGF) through the BBB. Methods: A middle cerebral artery occlusion (MCAO) model was first established. We chose different stimulation time courses and observed the effects of EA treatment (100 Hz frequency; 2 mA intensity) at GV20 and GV26 on the BBB in rats recovering from MCAO 3 weeks after modelling. The rats were injected with 2% Evans blue (EB) saline. The brain water content was measured using a wet/dry weighing method. The degree of penetration of EB was detected using spectrophotometry and laser confocal microscopy. The rats were then injected with NGF, and the concentration of NGF in the brain tissues was measured using ELISA. Results: The increase in the BBB permeability was most notable following the 8 min EA stimulation (P<0.05), which may be advantageous for the targeted delivery of drugs (such as NGF) into the brain. Additionally, this effect did not appear to cause brain oedema (P>0.05) in healthy or MCAO rats. Conclusions: EA treatment for a certain stimulation time at GV20 and GV26 in MCAO rats can increase BBB permeability.